Analysis of Potential Hazards in the Production Process of Railway Passenger Benches Using Hazard Identification, Risk Assessment and Risk Control (HIRARC) and Fault Tree Analysis (FTA) Methods Case Study: PT. Empat Putera Utama Bersama - Pambudi, Danang Bagus; HM, Gatot Basuki (Jurnal Teknologi dan Manajemen, 2025)
The increasing competition of companies requires a company to optimize all existing human resources (HR) to minimize risks that can hinder production process activities, PT. Four Putera Utama Bersama is a company engaged in the production of train passenger seats. There are several activities, namely preparation, production, assembly and finishing. The purpose of this study is to find out the type of hazard, and risk assessment with the HIRIARC method, while the FTA method is used to find the root cause of the problem. The results of the analysis will be used to mitigate any risk activities that occur in the production process of train passenger seats. The results of the study showed that there were 4 work activities and 11 work sub-activities that had potential dangers in activities. Risk assessment was obtained 3 activities with potential hazards in the extreme category, 2 activities with potential hazards in the high category, 2 activities with potential hazards in the moderate category  and 4 activities with potential hazards in the lowcategory, risk control was carried out on potential hazards that had extreme categoriesnamely pinched by the bench, hands hit by cutters and hands scratched by the bench frame that is still sharp.